Changes in skin barrier integrity by electrical impedance spectroscopy during dupilumab treatment on a child with severe atopic dermatitis - Elif Yaycı; Işıl Ezelsoy; Beliz Su Gündoğdu; Betül Büyüktiryaki; Cansın Saçkesen (The Turkish Journal of Pediatrics)
Background. Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by epidermal skin barrier dysfunction and altered immune response. Electrical impedance spectroscopy (EIS) has been used as a novel tool to detect skin barrier changes in AD. EIS is a non-invasive measure of the electrical impedance of tissue and is sensitive to cellular structure and extracellular environment.